Dynamic Relationship Between Financial Development and Economic Growth in Asian Economies: A GMM Analysis - Rahman, Ashiqur (2026)
Strong financial systems that increase productivity, promote innovation, and allow resources to be reallocated efficiently across different sectors underpin sustained economic growth in countries at various stages of development. In fact, a vibrant financial sector supports innovation, economic stability, and resilience to financial shocks. However, this is not the case for all countries. While financial institutions in developed countries tend to adjust quickly to new circumstances, those in developing countries often lack the strength to overcome hurdles to sound financial systems. Therefore, it is acknowledged that financial institutions play a major role in economic growth. This paper investigates the role of financial institutions in economic growth by analyzing the data of 27 Asian countries from 2002 to 2021. In order to do so, the paper employs a two-step System GMM estimation methodology. The paper finds that the impact of these variables differs across countries. For instance, variables like asset profitability, liquidity depth, and market trading activity are found to be positively and significantly related to growth in GDP per capita. Besides, lending to the private sector is found to be negatively related to growth, which may indicate inefficiencies in how credit is allocated in some countries. Hence, the paper concludes that since enhancements in the performance of financial systems and liquidity of equity markets support economic growth, it would be prudent for policymakers to make the strengthening of financial frameworks their top priority if they want to attain sustainable development over the long term.